PENGARUH LITERASI PAJAK, SISTEM ADMINISTRASI PAJAK DIGITAL, SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM YANG TERDAFTAR DI KPP PRATAMA MEDAN POLONIA - Kumala Dewi, Sri (Worksheet : Jurnal Akuntansi, 2025)
Indonesia is a developing country with a large and advanced number of companies in various industrial sectors that support economic growth. The existence of Micro, Small, and Medium Enterprises (MSMEs) is one strategy to encourage the country's economic growth. Both in terms of the number of companies that have been operating and job creation, MSMEs are very helpful to the Indonesian economy. The purpose of this study is to determine whether there is an influence of tax literacy, digital tax administration systems, tax sanctions on taxpayer compliance of MSMEs registered at the Medan Polonia Pratama Tax Office. This study uses a quantitative method with a sample of 95 respondents. This study uses data quality tests, classical assumption tests, multiple linear analysis, determinant coefficient tests and hypothesis tests. The results of the study indicate that partially the tax literacy variable has a positive and significant effect on taxpayer compliance, the digital tax administration system variable has a positive but insignificant effect on taxpayer compliance, while the tax sanctions variable has a positive and significant effect on taxpayer compliance. Simultaneously, the variables of tax literacy, digital tax administration system, tax sanctions on the compliance of MSME taxpayers registered at the Medan Polonia Pratama Tax Office have a significant positive influence on the compliance of MSME taxpayers registered at the Medan Polonia Pratama Tax Office.Keyword: Tax Literacy, digital tax administration system, tax sanctions, taxpayer compliance, KPP Pratama Medan Polonia